A survey of certain aspects of the share-milking industry in the Waikato, 1945/46 being a thesis presented by "547" in partial fulfilment of the requirements of the M. Ag. Sc. Degree - Milliken, M. (Massey University, 1947)
Associated with the outstanding development of the dairy industry in New Zealand over the years of this century has been the rapid growth of that section of dairying known as share-milking. The term 'share-miIking', in this country, applies to that type of dairy farm labour, the wages for which are based upon some proportion of the proceeds of the sale of farm produce. This general definition covers in New Zealand three principal systems of share-farming: (a) 'Quarter share-milking', where the farm owner supplies the land and capital (including the herd) and the share-milker supplies only the labour required for the milking and care of the stock. He does not do general farm maintenance except for added remuneration and received, at the time to which this study applies, 271/2% of the proceeds of the sale of dairy products and half the proceeds of the by-products. (b) 'Third share-milking, where the farm owner supplies the land and capital (including the herd) and the share-milker provides the labour for, and does, the general farm maintenance in addition to the milking and care of the stock. His share of the receipts was (at the time to which this applies) 36-2/3% of the dairy cheque and half the proceeds from the sale of by-products. (c) 'Half share-milking', where the farm owner supplies the land and fixed capital and the share-milker supplies the herd in addition to all the farm labour. He generally receives half the dairy cheque and half the proceeds from the sale of by-products. This division may be and often is, varied as there is no Statutory Regulation for this type of agreement. See Appendix II for the regulations covering the proportionate receipts and payments of each of the two parties under the first two types of agreement. A popular half share agreement is also appended.
Keywords: Sharemilking; Dairy farming; Dairying